How does the pandemic facilitate mobile payment? - Zhao, Yuyang (2021)
Zhao, Y., & Bacao, F. (2021). How does the pandemic facilitate mobile payment? : An investigation on users’ perspective under the COVID-19 pandemic. International Journal of Environmental Research and Public Health, 18(3), 1-22. [1016]. https://doi.org/10.3390/ijerph18031016